Model Implementasi Kurikulum Diera Pendidikan Jarak Jauh: Penelitian - Gifari, Hafid Al; Andini, Dwi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze adaptive curriculum implementation models in the era of distance education as a response to post-pandemic learning transformation. The research employed a qualitative approach using library research through the analysis of primary literature, including journal articles, policy reports, and books published between 2014 and 2024. The findings reveal that the effectiveness of distance curriculum implementation depends on four key pillars: curriculum design flexibility, teachers’ digital readiness, students’ self-directed learning, and continuous evaluation. Supporting factors such as adaptive policies, digital infrastructure, and technological literacy also play crucial roles in the success of adaptive digital curriculum models. This study contributes to strengthening theoretical understanding and provides practical recommendations for educators and policymakers in enhancing Indonesia’s distance learning ecosystem.